Nutrition and brain: 5th Nestlé Nutrition Workshop, Mexico City, March 2000 - Fernstrom, John D. (Nestlé Nutrition Institute workshop series, 2001)
This volume provides a survey of the links between nutrition and the brain. It examines many of the mechanisms by which diet and individual nutrients are known to modify brain development, biochemistry and function, and evaluates current practices in the use of the diet for the prevention and treatment of disorders affecting brain function. It also highlights the need to consider issues related to brain function in the development and evolution of national policies for treating nutritional deficiencies and excesses. Written by leading investigators and clinicians, this publication will help practitioners, clinical investigators and scientists appreciate the broad opportunities awaiting investigation, and ultimately, clinical applications, in this dynamic and expanding area of investigation